Step
*
1
of Lemma
bag-remove1-member
1. T : Type
2. eq : EqDecider(T)
3. x : T
4. bs : Base
5. b1 : Base
6. bs = b1 ∈ pertype(λas,bs. ((as ∈ T List) ∧ (bs ∈ T List) ∧ permutation(T;as;bs)))
7. bs ∈ T List
8. b1 ∈ T List
9. permutation(T;bs;b1)
10. as : bag(T)
11. ({x} + bs) = ({x} + as) ∈ bag(T)
12. bag-remove1(eq;{x} + bs;x) = (inl as) ∈ (bag(T)?)
⊢ bag-remove1(eq;{x} + bs;x) = (inl b1) ∈ (bag(T)?)
BY
{ (NthHypEqTrans (-1) THEN EqCDA) }
1
.....subterm..... T:t
1:n
1. T : Type
2. eq : EqDecider(T)
3. x : T
4. bs : Base
5. b1 : Base
6. bs = b1 ∈ pertype(λas,bs. ((as ∈ T List) ∧ (bs ∈ T List) ∧ permutation(T;as;bs)))
7. bs ∈ T List
8. b1 ∈ T List
9. permutation(T;bs;b1)
10. as : bag(T)
11. ({x} + bs) = ({x} + as) ∈ bag(T)
12. bag-remove1(eq;{x} + bs;x) = (inl as) ∈ (bag(T)?)
⊢ as = b1 ∈ bag(T)
Latex:
Latex:
1.  T  :  Type
2.  eq  :  EqDecider(T)
3.  x  :  T
4.  bs  :  Base
5.  b1  :  Base
6.  bs  =  b1
7.  bs  \mmember{}  T  List
8.  b1  \mmember{}  T  List
9.  permutation(T;bs;b1)
10.  as  :  bag(T)
11.  (\{x\}  +  bs)  =  (\{x\}  +  as)
12.  bag-remove1(eq;\{x\}  +  bs;x)  =  (inl  as)
\mvdash{}  bag-remove1(eq;\{x\}  +  bs;x)  =  (inl  b1)
By
Latex:
(NthHypEqTrans  (-1)  THEN  EqCDA)
Home
Index